Scale-dependent trends in the investment of leaf domatia. (7th December 2021) - Biddick, Matthew
Abstract: Theory predicts that plants invest in defences proportional to the value or amount of tissue at risk. Domatia-bearing plants house predatory arthropods that defend against insect and fungal attack. Though leaf domatia represent a direct investment in the defence of leaf tissues, it remains unknown whether domatia production scales with amount of tissue at risk. I investigated how domatia investment scales with leaf size in 20 species of trees and shrubs from the south-west Pacific. Large-leaved species produced more domatia than smaller leaved species. However, domatia production did not consistently scale with leaf area among individuals of the same species, illustrating that trends in domatia investment are scale-dependent. Overall results suggest the processes modulating the allocation of resources to defence at the interspecific level are distinct from those operating at the intraspecific level.